Strategies for Institutional Strengthening of an Autonomous Business Unit of an Oil Palm Cooperative in Riau Province - Shinta Widyaningtyas; Yahya Yudhi Irawan; Muhammad Arwani; Ririn Fatma Nanda; Syifa Robbani (Universitas Darussalam Gontor, 2026)
The sustainability of oil palm smallholder institutions remains a major challenge in Indonesia due to fluctuating global market conditions, increasing production costs, limited managerial capacity, and uneven adoption of sustainable cultivation practices. Autonomous business units under oil palm cooperatives play an important role in coordinating production, marketing, and institutional support for smallholder farmers in Riau Province. However, these institutions continue to face several operational constraints, including limited technical competencies among members, insufficient implementation of occupational health and safety practices, suboptimal productivity, and limited extension services. These conditions may reduce institutional competitiveness and weaken the long-term sustainability of smallholder palm oil farming systems. Therefore, this study aimed to formulate and prioritize institutional strengthening strategies for an Autonomous Business unit of an oil palm cooperative in Riau Province, Indonesia. This research employed an integrated SWOT (Strengths, Weaknesses, Opportunities, Threats) and Quantitative Strategic Planning Matrix (QSPM) approach. SWOT analysis was used to identify internal and external strategic factors, while QSPM was applied to quantitatively determine priority strategies. The results indicate that the autonomous business unit demonstrates a relatively strong internal condition (IFE score = 3.172) and strong responsiveness to external factors (EFE score = 3.339), placing the institution in Quadrant I (Grow and Build) of the Internal–External Matrix. Six alternative strategies were generated through the SWOT matrix. The primary priority strategy identified through QSPM is improving human resource quality through cultivation and harvesting training (TAS = 7.31), followed by strengthening internal management (TAS = 7.08) and expanding partnership networks to enhance bargaining power (TAS = 6.92). These findings were demonstrated that strengthening technical capacity and institutional governance is essential for improving the competitiveness, resilience, and sustainability of oil palm smallholder institutions.